2022
DOI: 10.1101/2022.04.06.22272747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal lung function assessment of patients hospitalised with COVID-19 using1H and129Xe lung MRI

Abstract: IntroductionMicrovascular abnormalities and impaired 129Xe gas transfer have been observed in patients with COVID-19. The progression of pathophysiological pulmonary changes during the post-acute period in these patients remains unclear.MethodsPatients who were hospitalised due to COVID-19 pneumonia underwent a pulmonary 1H and 129Xe MRI protocol at 6, 12, 25 and 50 weeks after hospital admission. The imaging protocol included: ultra-short echo time, dynamic contrast enhanced lung perfusion, 129Xe lung ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…With respect to gas‐exchange, a combination of lung perfusion abnormalities and/or alveolar/interstitial endothelial changes may be mechanistically driving the observation of diminished RBC:membrane values. This is supported by the correlations detected for the changes in 129 Xe gas transfer with changes in pulmonary blood volume in one of the longitudinal studies 129 Xe gas‐exchange MRI 78 . Pilot dynamic contrast‐enhanced MRI evidence of pulmonary microvasculature abnormalities in 10 participants, after SARS‐CoV‐2 infection 90 also supports this hypothesis.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…With respect to gas‐exchange, a combination of lung perfusion abnormalities and/or alveolar/interstitial endothelial changes may be mechanistically driving the observation of diminished RBC:membrane values. This is supported by the correlations detected for the changes in 129 Xe gas transfer with changes in pulmonary blood volume in one of the longitudinal studies 129 Xe gas‐exchange MRI 78 . Pilot dynamic contrast‐enhanced MRI evidence of pulmonary microvasculature abnormalities in 10 participants, after SARS‐CoV‐2 infection 90 also supports this hypothesis.…”
Section: Discussionmentioning
confidence: 65%
“…The most comprehensive longitudinal study of 129 Xe MRI gas-exchange values was reported in the original nine participants with COVID. 78 As shown in Fig. 7, at 12-week follow-up, there was improved 129 Xe MRI RBC:membrane, but no longitudinal change was detected between 12 and 52 weeks, and median values remained abnormally lower than expected and than an age-and sex-matched healthy volunteer group of 12 participants.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations